2021
DOI: 10.3389/fimmu.2021.774433
|View full text |Cite
|
Sign up to set email alerts
|

Citrus reticulatae pericarpium Extract Decreases the Susceptibility to HFD-Induced Glycolipid Metabolism Disorder in Mice Exposed to Azithromycin in Early Life

Abstract: BackgroundStudies have shown that gut microbe disorder in mice due to early-life antibiotic exposure promotes glycolipid metabolism disorder in adulthood. However, the underlying mechanism remains unclear and there is not yet an effective intervention or treatment for this process.PurposeThe study investigated whether early-life azithromycin (AZT) exposure in mice could promote high-fat diet (HFD)-induced glycolipid metabolism disorder in adulthood. Moreover, the effect of citrus reticulata pericarpium (CRP) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…72 Furthermore, bacteria like Oscillospira and Prevotella, which showed increased abundance in the HVA and HRA groups, have been associated with beneficial effects on lipid metabolism and liver damage, including the reduction of TC, TG, LDL-C, ALT, and AST levels, as well as the increase of HDL-C levels, which is consistent with our results. 73,74 These findings indicated that the changes observed in the abundance of specific bacterial taxa in our study could potentially contribute to the beneficial effects of VA and RA supplementation on obesity, liver damage, glucose tolerance, insulin resistance, lipid profile, and inflammation in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 56%
“…72 Furthermore, bacteria like Oscillospira and Prevotella, which showed increased abundance in the HVA and HRA groups, have been associated with beneficial effects on lipid metabolism and liver damage, including the reduction of TC, TG, LDL-C, ALT, and AST levels, as well as the increase of HDL-C levels, which is consistent with our results. 73,74 These findings indicated that the changes observed in the abundance of specific bacterial taxa in our study could potentially contribute to the beneficial effects of VA and RA supplementation on obesity, liver damage, glucose tolerance, insulin resistance, lipid profile, and inflammation in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 56%
“…Colidextribacter has been reported to produce inosine, which ameliorates acute liver injury and inflammation caused by lipopolysaccharides ( Guo et al, 2021 ). Bilophila , a lipopolysaccharide-producing bacterium, exacerbates HFD-induced inflammation and causes metabolic disturbances in mice ( Lu et al, 2021 ). Low-grade chronic mild inflammation was a feature of obesity, and pathogenic gut microbes stimulate the production and release of LPS from intestinal epithelial cells, which subsequently bind to cytokine receptors and promote the release of pro-inflammatory cytokines ( Musso et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to healthy individuals, the levels of Megamonas in the guts of obese and ASD patients are significantly higher [ 56 , 57 ]. Sutterella is one of the most prevalent Proteobacteria , and its relative abundance was dramatically elevated in obese patients, implying its involvement in the onset and development of obesity [ 58 , 59 ]. In general, we have demonstrated that SFN can improve the composition of human gut microflora by suppressing the growth of pathogenic bacteria, while maintaining the equilibrium of beneficial intestinal flora.…”
Section: Resultsmentioning
confidence: 99%